The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.3346/jkms.2003.18.2.196
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Hypoxia Inducible Factor-1 alpha and Tumor Cell Proliferation Between Squamous Cell Carcinomas and Adenocarcinomas Among Operable Non-Small Cell Lung Carcinomas

Abstract: This study aimed to evaluate whether the elevated level of hypoxia-inducible factor-1 (HIF-1 ) correlated with histologic types, angiogenesis, tumor cell proliferation, and clinical parameters in common non-small cell lung carcinomas (NSCLCs). We performed immunohistochemical stains using paraffin-embedded tissue blocks from 84 cases of operable NSCLC [No. of squamous cell carcinoma (SCC), 45; No. of adenocarcinoma (AC), 39]. HIF-1 expression was related with histologic types (66.7% in SCCs vs 20.5% in ACs, p<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
(27 reference statements)
3
22
1
Order By: Relevance
“…However, there was no significant relationship between HIF-1a overexpression and survival of all NSCLC patients. Our findings are supported by those of Lee et al (2003) who showed no association between HIF-1a expression and overall survival in 84 NSCLC patients. In contrast to our results, other groups reported a significant relationship between HIF-1a expression and shorter survival (Swinson et al, 2004;Kim et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…However, there was no significant relationship between HIF-1a overexpression and survival of all NSCLC patients. Our findings are supported by those of Lee et al (2003) who showed no association between HIF-1a expression and overall survival in 84 NSCLC patients. In contrast to our results, other groups reported a significant relationship between HIF-1a expression and shorter survival (Swinson et al, 2004;Kim et al, 2005).…”
Section: Discussionsupporting
confidence: 82%
“…This finding is at variance with previous reports (35), although the prognosis after resection of the various histologic subtypes is still a subject of debate (36,37). In the present series, a positive correlation was observed between squamous cell carcinoma histology and EPO-R expression, which can be compared with a previously described association between this histology and hypoxiainduced factor-1a expression (38). The effect of hypoxia and anemia on EPO-R/EPO expression in tumor cells has not been fully evaluated.…”
Section: Resultscontrasting
confidence: 57%
“…However, association of HIF-1α with clinicopathological characteristics and prognosis is inconsistent. Previous studies reported that HIF-1α expression in NSCLC was marginally associated with histological types, T-stage and poor prognosis (Lee et al, 2003;Swinson et al, 2004). There are several possible reasons for the inconsistency.…”
Section: Discussionmentioning
confidence: 71%